Computational Modeling of Multi-Purpose Amphibious Aircraft Be-103 - Abbasov, Iftikhar B; Orekhov, V’iacheslav V (Review of Computer Engineering Research, 2017)
The paper is dedicated to the aspects of 3D computational modeling of Be-103 amphibious aircraft. The paper contains initial Figures and drawings; the computational modeling is performed in 3 ds Max 3D graphic modeling system. Models of amphibious aircraft structural components are produced by polygonal extrusion process. Shading is performed at the sub-objects level as well as assignment of materials. Figures illustrating realistic rendering of amphibious aircraft 3D-model are presented as well.